Neofusicoccum parvum Colonization of the Grapevine Woody Stem Triggers Asynchronous Host Responses at the Site of Infection and in the Leaves - Massonnet, Mélanie; Figueroa-Balderas, Rosa; Galarneau, Erin R. A.; Miki, Shiho; Lawrence, Daniel P.; Sun, Qiang; Wallis, Christopher M.; Baumgartner, Kendra; Cantu, Dario (Frontiers in Plant Science, 2017)
Grapevine trunk diseases cause important economic losses in vineyards worldwide. Neofusicoccum parvum, one of the most aggressive causal agents of the trunk disease Botryosphaeria dieback, colonizes cells and tissues of the grapevine wood, leading to the formation of an internal canker. Symptoms then extend to distal shoots, with wilting of leaves and bud mortality. Our aim was to characterize the transcriptional dynamics of grapevine genes in the woody stem and in the leaves during N. parvum colonization. Genome-wide transcriptional profiling at seven distinct time points (0, 3, and 24 hours; 2, 6, 8, and 12 weeks) showed that both stems and leaves undergo extensive transcriptomic reprogramming in response to infection of the stem. While most intense transcriptional responses were detected in the stems at 24 hours, strong responses were not detected in the leaves until the next sampling point at 2 weeks post-inoculation. Network co-expression analysis identified modules of co-expressed genes common to both organs and showed most of these genes were asynchronously modulated. The temporal shift between stem vs. leaf responses affected transcriptional modulation of genes involved in both signal perception and transduction, as well as downstream biological processes, including oxidative stress, cell wall rearrangement and cell death. Promoter analysis of the genes asynchronously modulated in stem and leaves during N. parvum colonization suggests that the temporal shift of transcriptional reprogramming between the two organs might be due to asynchronous co-regulation by common transcriptional regulators. Topology analysis of stem and leaf co-expression networks pointed to specific transcription factor-encoding genes, including WRKY and MYB, which may be associated with the observed transcriptional responses in the two organs.